경기북부 개별사업장 및 공공하 · 폐수처리장의 노닐페놀, 옥틸페놀 거동특성 연구 - 윤수현; Su-hyun Yoon; 정종필; Jong-pil Jung; 서인숙; In-suk Seo; 김지영; Ji-young Kim; 김수현; Su-hyun Kim; 유한조; Hanjo You; et al. (환경분석과 독성보건, 2024)
This study examines the emission characteristics of nonylphenol (NP) and octylphenol (OP) in the discharged water of Northern Gyeonggi Province, South Korea, where the textile industry predominates. We evaluated 104 individual wastewater discharge facilities, six public wastewater treatment plants (WWTPs), and the Shincheon River. Our findings reveal that NP and OP concentrations were notably high in the textile industry, with median levels of 0.53 μg/L and 0.43 μg/L, respectively, in individual wastewater discharge facilities. Furthermore, monitoring NP and OP levels in the influent and effluent of WWTPs and river water demonstrated that WWTP effluent has a remarkable impact on NP and OP concentrations in the river. The removal rates of NP and OP in WWTPs averaged 69.6% and 41.8%, respectively, and these rates tended to increase with higher temperatures and influent concentrations. The average concentrations in the Shincheon River were 0.31 μg/L for NP and 0.45 μg/L for OP, slightly exceeding EU standards. It is essential to closely monitor NP and OP levels to protect aquatic ecosystems.